2019
DOI: 10.25307/jssr.620393
|View full text |Cite
|
Sign up to set email alerts
|

Elit Güreşçilerin Doping ve Ergojenik Yardım Hakkındaki Bilgi ve Kullanma Düzeylerinin İncelenmesi

Abstract: Çalışmanın amacı; Türkiye Serbest, Greko-Romen ve kadın Milli Takım güreşçilerinin doping ve ergojenik yardım hakkındaki bilgi düzeyleri ve tutumlarının incelenmesidir. Araştırmaya 2019 yılında milli takım kamplarında yer alan 47 Serbest stil, 52 Greko-Romen stil ve 24 kadın olmak üzere toplam 123 elit güreşçi gönüllü olarak katılmışlardır. Çalışmaya katılan sporcuların yaş ortalamalarının 22,94±3,44 yıl olduğu tespit edilmiştir. Çalışmada Eröz (2007) tarafından geliştirilen, doping maddeleri ve ergojenik yard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…In the research, when the scores of athletes with higher years of sports experience were examined, it was found that athletes with greater sports experience had higher knowledge levels. Yıldırım and Şahin (16) in their study found a statistically significant negative relationship in the comparison of years of sports experience regarding the statement "I try every means to succeed in sports" and the most commonly used stimulants in sports, such as caffeine and cocaine. Similarly, in a study by Gençtürk, at al.…”
Section: Discussionmentioning
confidence: 94%
“…In the research, when the scores of athletes with higher years of sports experience were examined, it was found that athletes with greater sports experience had higher knowledge levels. Yıldırım and Şahin (16) in their study found a statistically significant negative relationship in the comparison of years of sports experience regarding the statement "I try every means to succeed in sports" and the most commonly used stimulants in sports, such as caffeine and cocaine. Similarly, in a study by Gençtürk, at al.…”
Section: Discussionmentioning
confidence: 94%
“…Her ne kadar bu durum sporcuları olimpizm felsefesinden yani erdemli ya da ahlaklı insan yaratma idealinden uzaklaştırsa da daha önce kırılmış rekorları kırmanın gittikçe zorlaşması, rekor için saliselerin, milimlerin, gramların önem kazanması, sporun yapılışına uygun olmayan yöntemlerin kullanılmasına yol açmaktadır (Yıldırım ve Şahin, 2019). Kullanılan bu maddeler ve yöntemler sporcularda ciddi sağlık problemlerine neden olmakta hatta ölümle bile sonuçlanmaktadır.…”
Section: Introductionunclassified